Dynamic Speckle Laser Technique for the Characterization of Electrotechnical-porcelain - Salguero, Facundo J. (2015)
This work analyzes the quality of two types of commercial electro-technical-porcelain using textural and physical-chemical methods: BET surface area and pore size by gas adsorption, X-ray powder di®raction; Electronic Microscopy and Energy dispersive X-ray analysis, Infrared Spectroscopy and their water adsorption capacity by the Dynamic Speckle Laser technique. Experimental results showed the evolution of the speckle patterns during hydro-adsorption pro- cess, permitting to discriminate di®erent behavior for each material. It was determined that it is possible to correlate changes in the speckle patterns with the porosity and chemical composition of materials.